Subtle structural alterations in G-quadruplex DNA regulate site specificity of fluorescence light-up probes. Issue 3 (8th January 2020) - Kumar, Rajendra; Chand, Karam; Bhowmik, Sudipta; Das, Rabindra Nath; Bhattacharjee, Snehasish; Hedenström, Mattias; Chorell, Erik
Abstract: G-quadruplex (G4) DNA structures are linked to key biological processes and human diseases. Small molecules that target specific G4 DNA structures and signal their presence would therefore be of great value as chemical research tools with potential to further advance towards diagnostic and therapeutic developments. However, the development of these types of specific compounds remain as a great challenge. In here, we have developed a compound with ability to specifically signal a certain c-MYC G4 DNA structure through a fluorescence light-up mechanism. Despite the compound's two binding sites on the G4 DNA structure, only one of them result in the fluorescence light-up effect. This G-tetrad selectivity proved to originate from a difference in flexibility that affected the binding affinity and tilt the compound out of the planar conformation required for the fluorescence light-up mechanism. The intertwined relation between the presented factors is likely the reason for the lack of examples using rational design to develop compounds with turn-on emission that specifically target certain G4 DNA structures. However, this study shows that it is indeed possible to develop such compounds and present insights into the molecular details of specific G4 DNA recognition and signaling to advance future studies of G4 biology.